Self‐Generating High‐Temperature Oxidation‐Resistant Glass‐Ceramic Coatings for C–C Composites Using UHTCs. Issue 9 (4th July 2014) - Walker, Luke S.; Corral, Erica L.; Parthasar, T.
<x xml:space="preserve">Abstract</x> Carbon–carbon (C–C) composites are ideal for use as aerospace vehicle structural materials; however, they lack high‐temperature oxidation resistance requiring environmental barrier coatings for application. Ultra high‐temperature ceramics (UHTCs) form oxides that inhibit oxygen diffusion at high temperature are candidate thermal protection system materials at temperatures >1600°C. Oxidation protection for C–C composites can be achieved by duplicating the self‐generating oxide chemistry of bulk UHTCs formed by a "composite effect" upon oxidation of ZrB2–SiC composite fillers. Dynamic Nonequilibrium Thermogravimetric Analysis (DNE‐TGA) is used to evaluate oxidation in situ mass changes, isothermally at 1600°C. Pure SiC‐based fillers are ineffective at protecting C–C from oxidation, whereas ZrB2–SiC filled C–C composites retain up to 90% initial mass. B2O3 in SiO2 scale reduces initial viscosity of self‐generating coating, allowing oxide layer to spread across C–C surface, forming a protective oxide layer. Formation of a ZrO2–SiO2 glass‐ceramic coating on C–C composite is believed to be responsible for enhanced oxidation protection. The glass‐ceramic coating compares to bulk monolithic ZrB2–SiC ceramic oxide scale formed during DNE‐TGA where a comparable glass‐ceramic chemistry and surface layer forms, limiting oxygen diffusion.